Gender Equality, Climate Action, and Technological Innovation for Sustainable Development in Africa - Adeola, Ogechi (Sustainable Development Goals Series, 2024)
This open access book explores the intersection of gender and climate change, suggests ways in which innovative technologies can accelerate climate relief actions, and offers strategies for integrating climate change initiatives into national policies and planning. By examining the devastating consequences of climate change on women and girls throughout the continent, the authors pose a crucial question: Does gender matter in climate change discussions in Africa? Political and social traditions have burdened women with greater vulnerability to the impacts of climate-related natural disasters, including violence, displacement, poverty, famine and lack of access to clean water. However, women are also key to effective and inclusive climate mitigation, adaptation, and decision-making. The authors provide a compelling discourse that identifi es the social and economic benefi ts for all citizens when genderinclusive policies shape equitable and targeted action plans, from mitigationto adaptation and funding. The UN's SDG 13 calls for urgent action and commitment to combat climate change. The implementable and action-oriented propositions presented in this book will be of interest to students, educators, practitioners, third-sector actors, and policymakers committed to gender equality, sustainable development and climate action in Africa.